Melacak Eksistensi Kosakata Mesir Kuno dalam Al-Qur'an - Iffa Nurul Laili (JOURNAL OF QUR'AN AND HADITH STUDIES, 2014)
There has been a shift of paradigm between the classical Muslim scholars and the modern Muslim scholars in analyzing the Qur’an. The classical scholars preferred theological paradigm, while the modern scholars prefer academic and critical studies. In analyzing the Arabicity of Qur’anic language, the classical scholars argued that all language of the Qur’an are pure Arabic language. They based their argument on the verses of the Qur’an, and also on the theological view on the origin of Qur’anic language.  The modern scholars, on the other hand, argue for the existence of foreign words in the Qur’an. This view is based on the fact that the Qur’anic language is historical and cultural language, eventhough they do not deny its divine origin. In this article, the writer analyzes the view of Sa’d ‘Abd al-Mutallib al-‘Adl in his al-Hiruglifiyah Tufassir Al-Qur'an Sharh ma Yusamma bi al-Huruf al-Muqatta’ah which seeks to find the historical root of the Qur’an in Old Egyptian civilization to prove the use of Old Egyptian terms in the Qur’an.